Aspects ofthe prevalence of congenital heart diseases in early age children in the Republic of Tajikistan - N. K. Kuzibaeva (Лечащий Врач)
In recent years congenital heart diseases have taken a leading position in terms of prevalence in comparison with other malformations in children and remain the leading cause of their death. In addition, a further increase in the prevalence of congenital heart diseases is predicted. The aim of the study was to study the incidence of congenital heart diseases among children according to children's cardiologic departments nmts Republic of Tajikistan. For the period from 2010 to 2014, the total number of admitted patients with congenital heart diseases and who were hospitalized in the pediatric cardiorheumatology nmts Republic of Tajikistan was – 5100, of them, with congenital heart diseases – 1486. The age of the patients ranged from 2 months to 15 years. There were 57% of boys and 43% of girls. All children who were admitted to the hospital for examination and treatment, in addition to measuring anthropometric parameters, were carried out additional research methods to confirm the diagnosis. In the study of congenital heart diseases prevalence in the regions and districts of the Republic, in appealing and hospitalization in children's cardio-rheumatology, revealed a tendency to increase of confirmed congenital heart diseases in districts of Republican subordination – 620, in Khatlon 379, Dushanbe – 439. The average number of patients admitted from Sughd region was 43 patients and the lowest number of patients admitted for treatment was from Gorno-Badakhshan Autonomous Region – only 5 children. During the period from 2010 to 2014, the epidemiology of congenital heart diseases in young children was analyzed, which indicated a tendency to increase in sick children with congenital heart diseases by year throughout the republic. The most vulnerable, according to the prevalence of congenital heart diseases, was the southern region of the republic, the disease was least common in Gorno-Badakhshan Autonomous Region. The most common congenital heart diseases were ventricular and interatrial septal defects and Fallot's tetrad. The obtained data will contribute to the development of measures to improve early diagnosis and timely correction of the identified pathology.